The Long Term Effect of Education Spending Decentralization on Human Capital in Spain - Ouarda Merrouche (Uppsala University, Department of Economics, 2007)
In 1980, seven out of the seventeen Spanish regions were devolved education spending responsibility. Using a difference-in-differences approach, which I show to be particularly credible in this context, I evaluate the long term effect of this reform on human capital. I find no robust evidence to corroborate the theoretically predicted benefits of decentralization.
urn:nbn:se:uu:diva-25354
Keywords: E61; E65; 330; Decentralization; Education; Difference-in-differences estimator; Öffentliche Ausgaben; Bildungsinvestition; Dezentralisierung; Bildungsertrag; Humankapital; Spanien